Optical Elements
By using a retardation plate with an alignment layer containing elemental fluorine or a surfactant, the alignment regulating force and retardation of liquid crystal layers are improved, addressing the limitations of existing methods in optical elements.
Patent Information
- Application Number
- JP2022541561
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-28
- Filing Date
- 2021-08-03
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2041-08-03
AI Technical Summary
Existing methods for orienting liquid crystal molecules in optical elements do not effectively enhance the alignment regulating force and retardation of liquid crystal layers.
Incorporating a retardation plate with a transparent base material, an alignment layer formed from an energy-curable composition containing elemental fluorine or a surfactant, and a liquid crystal layer with parallel grooves of specific dimensions to improve alignment and retardation.
The alignment regulating force of the alignment layer is enhanced, leading to increased retardation of the liquid crystal layer, reducing diffracted light and improving optical performance.
Smart Images

Figure 0007613470000011 
Figure 0007613470000012 
Figure 0007613470000013
Abstract
Description
[Technical field]
[0001] The present disclosure relates to optical elements. [Background technology]
[0002] The method for manufacturing an optical element described in Patent Document 1 involves (A) forming an alignment layer having a fine groove structure, (B) laminating a coating material exhibiting a liquid crystal phase on the alignment layer, and (C) solidifying the coating material layer to fix the alignment of the liquid crystal phase.
[0003] The liquid crystal device described in Patent Document 2 sandwiches liquid crystal molecules between a first substrate and a second substrate, and modulates light waves by the birefringence of the liquid crystal. A grating structure having a pitch shorter than the wavelength of the light waves is provided on the first substrate or the second substrate. The grating structure is formed by a nanoimprint method, and controls the alignment direction of the liquid crystal molecules and also controls the phase of the light waves that have passed through the liquid crystal.
[0004] The method for producing a liquid crystal alignment film described in Patent Document 3 includes the steps of injecting a liquid crystal substance onto a non-flat surface of an alignment film to form a liquid crystal layer. The method for producing an alignment film includes (A) transferring the concave-convex pattern of a mold onto a transfer layer, (B) forming a titanium dioxide layer on the concave-convex pattern, (C) deforming the titanium dioxide layer into a curved surface having a lens shape, and (D) etching the titanium dioxide layer deformed into a curved surface to form a fine concave-convex pattern on the curved surface. A liquid crystal substance is injected onto this concave-convex pattern. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japan Special Publication No. 2005-516236 [Patent Document 2] Japanese Patent Publication No. 2013-7781 [Patent Document 3] Japan Special Publication No. 2016-509966 Summary of the Invention [Problem to be solved by the invention]
[0006] Conventionally, in order to align liquid crystal molecules, formation of a fine groove structure in an alignment layer has been considered.
[0007] One aspect of the present disclosure provides a technique for improving the alignment control force of an alignment layer and increasing the retardation of a liquid crystal layer. [Means for solving the problem]
[0008] The optical element according to one embodiment of the present disclosure comprises: The retardation plate includes a retardation plate that is curved along a curved surface. The liquid crystal display device includes a transparent substrate, an alignment layer formed on the transparent substrate, and a liquid crystal layer formed on the alignment layer. A surface of the alignment layer in contact with the liquid crystal layer is formed with a plurality of parallel grooves for aligning liquid crystal molecules of the liquid crystal layer. The grooves have a pitch of 10 nm to 600 nm. The alignment layer is a copolymer of an energy curable composition, and the surface contains elemental fluorine. The depth of the groove at the portion where the retardation plate is thinnest is greater than the depth of the groove at the portion where the retardation plate is thickest.
[0009] Moreover, an optical element according to another aspect of the present disclosure includes: The retardation plate includes a retardation plate that is curved along a curved surface. The liquid crystal display device includes a transparent substrate, an alignment layer formed on the transparent substrate, and a liquid crystal layer formed on the alignment layer. A surface of the alignment layer in contact with the liquid crystal layer is formed with a plurality of parallel grooves for aligning liquid crystal molecules of the liquid crystal layer. The grooves have a pitch of 10 nm to 600 nm. The alignment layer is a copolymer of an energy curable composition and contains a surfactant. The depth of the groove at the portion where the retardation plate is thinnest is greater than the depth of the groove at the portion where the retardation plate is thickest. Effect of the Invention
[0010] According to one aspect of the present disclosure, the fluorine element or surfactant contained in the alignment layer can improve the alignment control force of the alignment layer, thereby increasing the retardation of the liquid crystal layer. [Brief description of the drawings]
[0011] [Figure 1]FIG. 1 is a cross-sectional view showing the optical element according to the first embodiment. [Diagram 2] FIG. 2(A) is a perspective view showing an example of a transparent substrate and an alignment layer, and FIG. 2(B) is a perspective view showing an example of liquid crystal molecules aligned by the alignment layer shown in FIG. 2(A). [Diagram 3] FIG. 3(A) is a cross-sectional view showing a state before a retardation plate and a lens of an optical element according to the second embodiment are bonded together, FIG. 3(B) is a cross-sectional view of an optical element formed by bonding the retardation plate and the lens shown in FIG. 3(A), and FIG. 3(C) is a plan view of the optical element shown in FIG. 3(B). [Figure 4] FIG. 4(A) is a cross-sectional view showing an optical element according to a first modified example of the second embodiment, FIG. 4(B) is a cross-sectional view showing an optical element according to a second modified example of the second embodiment, and FIG. 4(C) is a cross-sectional view showing an optical element according to a third modified example of the second embodiment. [Diagram 5] FIG. 5(A) is a cross-sectional view showing a state before a retardation plate and a lens of an optical element relating to a reference embodiment are bonded together, FIG. 5(B) is a cross-sectional view showing an optical element formed by bonding the retardation plate and the lens shown in FIG. 5(A), and FIG. 5(C) is a plan view showing the distribution of Rd of the optical element shown in FIG. 5(B). [Figure 6] FIG. 6(A) is a cross-sectional view showing a state before a retardation plate and a lens of an optical element relating to a modified example of the reference embodiment are bonded together, FIG. 6(B) is a cross-sectional view showing an optical element obtained by bonding the retardation plate and the lens shown in FIG. 6(A), and FIG. 6(C) is a plan view showing the distribution of Rd of the optical element shown in FIG. 6(B). [Figure 7] Figure 7(A) is a cross-sectional view of an optical element according to a third embodiment, Figure 7(B) is a cross-sectional view showing an enlarged view of region B in Figure 7(A), and Figure 7(C) is a cross-sectional view showing an enlarged view of region C in Figure 7(A). [Figure 8] Figure 8(A) is a cross-sectional view of an optical element related to a modified example of the third embodiment, Figure 8(B) is a cross-sectional view showing an enlarged view of region B in Figure 8(A), and Figure 8(C) is a cross-sectional view showing an enlarged view of region C in Figure 8(A). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. In each drawing, the same or corresponding configurations are denoted by the same reference numerals, and descriptions thereof may be omitted. In addition, in the specification, a numerical range indicated by "~" means that the numerical range indicated before and after the range includes the lower and upper limits.
[0013] (First embodiment) An optical element 1 according to a first embodiment will be described with reference to Fig. 1. The optical element 1 includes a retardation plate 3. The retardation plate 3 is, for example, flat. The retardation plate 3 includes, for example, a transparent substrate 4, an alignment layer 5 formed on the transparent substrate 4, and a liquid crystal layer 6 formed on the alignment layer 5.
[0014] The retardation plate 3 has a slow axis and a fast axis. When viewed in the Z-axis direction, the slow axis is in the X-axis direction and the fast axis is in the Y-axis direction. The slow axis is the direction in which the refractive index is greatest, and the fast axis is the direction in which the refractive index is smallest.
[0015] The retardation plate 3 is, for example, a quarter-wave plate. A quarter-wave plate may be used in combination with a linear polarizing plate (not shown). The absorption axis of the linear polarizing plate and the slow axis of the quarter-wave plate are arranged to be shifted by 45°. The linear polarizing plate and the quarter-wave plate constitute a circular polarizing plate.
[0016] The transparent substrate 4 is composed of, for example, a glass substrate or a resin substrate. The glass substrate or the resin substrate may have a reflecting or absorbing function for one or more of infrared rays, visible light, and ultraviolet rays, and may be configured to transmit light in a specific wavelength band. The transparent substrate 4 may have a single-layer structure of a single substrate, or may have a multi-layer structure in which a film that imparts a reflecting or absorbing function is laminated on a main substrate (glass substrate or resin substrate) to transmit light in a specific wavelength band. In addition, the transparent substrate 4 may be laminated with a film that imparts a function such as antifouling in addition to the reflecting or absorbing function.
[0017] For example, the transparent substrate 4 may further include a resin film or an inorganic film in addition to a glass substrate or a resin substrate. The resin film is a film having a function such as a color correction filter, a base film such as a silane coupling agent, or an antifouling film. The resin film is formed by, for example, screen printing, vapor deposition, spray coating, or spin coating. The inorganic film is, for example, a metal oxide film having a function as an optical interference film (antireflection or wavelength selection filter). The inorganic film is formed by, for example, sputtering, vapor deposition, or CVD.
[0018] From the viewpoint of bending processability, the transparent substrate 4 is preferably a resin substrate. Specific examples of the resin of the resin substrate include polymethylmethacrylate (PMMA), triacetylcellulose (TAC), cycloolefin polymer (COP), cycloolefin copolymer (COC), polyethylene terephthalate (PET), and polycarbonate (PC).
[0019] The phase difference (retardation) of the transparent substrate 4 is, for example, 5 nm or less, and preferably 3 nm or less. From the viewpoint of reducing the variation in color tone, the phase difference of the transparent substrate 4 is preferably smaller, and may be zero. The phase difference of the transparent substrate 4 is measured, for example, by a parallel Nicol rotation method.
[0020] The glass transition temperature Tgf of the transparent substrate 4 is, for example, 80° C. to 200° C., and preferably 90° C. to 160° C. If Tgf is within the above range, bending workability is good. The glass transition temperature of the transparent substrate 4 is measured, for example, by thermomechanical analysis (TMA).
[0021] The transparent substrate 4 has a thickness T1 (see FIG. 2) of, for example, 0.01 mm to 0.3 mm, preferably 0.02 mm to 0.1 mm, and more preferably 0.03 mm to 0.09 mm. When T1 is within the above range, bending workability and handleability can be compatible.
[0022] The alignment layer 5 aligns the liquid crystal molecules in the liquid crystal layer 6. A plurality of parallel grooves 52 are formed on a surface 51 of the alignment layer 5 that contacts the liquid crystal layer 6, for aligning the liquid crystal molecules in the liquid crystal layer 6. The plurality of grooves 52 are formed, for example, in a stripe pattern. When viewed in the Z-axis direction, the longitudinal direction of the grooves 52 is the X-axis direction, and the width direction of the grooves 52 is the Y-axis direction.
[0023] The parallelism of the grooves 52 is, for example, 0° to 5°, preferably 0° to 3°, and more preferably 0° to 1°. The parallelism of the grooves 52 is the maximum value of the angle between two adjacent grooves 52 when viewed in the Z-axis direction. The closer the angle between two adjacent grooves 52 is to 0°, the better the parallelism.
[0024] The depth D of the groove 52 is, for example, 3 nm to 500 nm, preferably 5 nm to 300 nm, and more preferably 10 nm to 150 nm. If D is 3 nm or more, the alignment control force is large, and the liquid crystal molecules are easily aligned. On the other hand, if D is 500 nm or less, the transferability of the concave-convex pattern of the mold is good. Also, if D is 500 nm or less, diffracted light is less likely to occur.
[0025] The pitch p of the grooves 52 is, for example, 10 nm to 600 nm, preferably 50 nm to 300 nm, and more preferably 80 nm to 200 nm. If p is 600 nm or less, the alignment control force is large and the liquid crystal molecules are easily aligned. If p is 300 nm or less, diffracted light is less likely to occur. On the other hand, if p is 10 nm or more, it is easy to form the concave-convex pattern of the mold.
[0026] The opening width W of the groove 52 is, for example, 5 nm to 500 nm, preferably 20 nm to 200 nm, and more preferably 30 nm to 150 nm. The difference between the pitch p and the opening width W (pW: p>W) is the distance between the grooves 52.
[0027] 2, the cross section of the groove 52 perpendicular to the longitudinal direction (X-axis direction) is rectangular, but it may be triangular. The shallower the depth of the groove 52 having a triangular cross section, the wider the width. In this case, it is easy to peel off the mold used in the imprint method.
[0028] The alignment layer 5 is a copolymer of an energy curable composition. The energy curable composition is a photocurable composition or a thermosetting composition. In particular, a photocurable composition is preferred because of its excellent processability, heat resistance, and durability. The photocurable composition is, for example, a composition containing a monomer, a photopolymerization initiator, a solvent, and additives (for example, a surfactant, a polymerization inhibitor, an antioxidant, an ultraviolet absorber, a light stabilizer, and an antifoaming agent) as required. As the photocurable composition, for example, those described in paragraphs 0028 to 0060 of Japanese Patent No. 5978761 are used. The photocurable composition contains, for example, a fluorine-containing monomer containing a fluorine element and a photocurable monomer not containing a fluorine element.
[0029] The alignment layer 5 contains elemental fluorine on the surface 51 in contact with the liquid crystal layer 6. The elemental fluorine is derived from a fluorine-containing monomer. The elemental fluorine tends to gather on the surface 51 of the alignment layer 5 rather than inside the alignment layer 5. The elemental fluorine reduces the surface free energy of the surface 51 of the alignment layer 5, and reduces the wettability of the liquid crystal composition described below. As a result, the liquid crystal composition is brought into the most energetically stable state, that is, the state in which the liquid crystal molecules are aligned in parallel. Therefore, the alignment control force of the alignment layer 5 can be improved, and the retardation of the liquid crystal layer 6 can be increased.
[0030] The fluorine element concentration FC of the surface 51 of the alignment layer 5 is, for example, 0.1 atomic % to 50 atomic %, preferably 1 atomic % to 40 atomic %, more preferably 2 atomic % to 30 atomic %, and further preferably 5 atomic % to 20 atomic %. When FC is 0.1 atomic % or more, the effect of improving the alignment control force can be obtained. On the other hand, when FC is 50 atomic % or less, clouding of the alignment layer 5 can be suppressed. In addition, when FC is 50 atomic % or less, the adhesion between the alignment layer 5 and the transparent substrate 4, and the adhesion between the alignment layer 5 and the liquid crystal layer 6 can be improved. For example, when the material of the alignment layer 5 is PTFE (polytetrafluoroethylene) and FC is 58 atomic %, when liquid crystal composition L1 (see the Example column) is applied to the alignment layer 5 by spin coating, the liquid crystal composition L1 does not adhere to the alignment layer 5 and peels off.
[0031] The alignment layer 5 may contain a surfactant instead of or in addition to elemental fluorine. The surfactant is uniformly dispersed in the alignment layer 5. The surfactant is, for example, fluorine-based or silicone-based. Like elemental fluorine, the surfactant reduces the surface free energy of the surface 51 of the alignment layer 5 and reduces the wettability of the liquid crystal composition described below. As a result, the liquid crystal composition is guided to the most energetically stable state, that is, the state in which the liquid crystal molecules are aligned in parallel. Therefore, the alignment control force of the alignment layer 5 can be improved, and the retardation of the liquid crystal layer 6 can be increased.
[0032] The surfactant content SC in the alignment layer 5 is, for example, 0.05% by mass to 4% by mass, preferably 0.1% by mass to 3% by mass, and more preferably 0.2% by mass to 2% by mass. When SC is 0.05% by mass or more, the effect of improving the alignment control force of the alignment layer 5 can be obtained. On the other hand, when SC is 4% by mass or less, the multiple components constituting the energy curable composition are easily mixed. Unlike monomers, surfactants are hardly polymerized. Therefore, when the energy curable composition does not contain a solvent, the surfactant content SC of the energy curable composition and the alignment layer 5 are approximately the same.
[0033] The alignment layer 5 is formed, for example, by an imprinting method. In the imprinting method, an energy curable composition is sandwiched between the transparent substrate 4 and a mold, the concave-convex pattern of the mold is transferred to the energy curable composition, and the energy curable composition is cured. By using the imprinting method, the size and shape of the grooves 52 can be precisely controlled, and the inclusion of foreign matter can also be reduced.
[0034] The energy curable composition may be applied onto the transparent substrate 4 or onto a mold. The application method may be a spin coating method, a bar coating method, a dip coating method, a casting method, a spray coating method, a bead coating method, a wire bar coating method, a blade coating method, a roller coating method, a curtain coating method, a slit die coating method, a gravure coating method, a slit reverse coating method, a microgravure method, a comma coating method, or the like.
[0035] The thickness T2 of the alignment layer 5 (see FIG. 2) is, for example, 1 nm to 20 μm, preferably 50 nm to 10 μm, and more preferably 100 nm to 5 μm. The thickness T2 of the alignment layer 5 is measured in the normal direction at each point of the surface 41 of the transparent substrate 4 on which the alignment layer 5 is formed. When the alignment layer 5 has a groove 52, in this specification, the thickness T2 of the alignment layer 5 refers to the distance between the bottom of the groove 52 and the surface 41 of the transparent substrate 4. If the thickness of the alignment layer is 20 μm or less, the processability is good.
[0036] The glass transition temperature Tg_al of the alignment layer 5 is, for example, 40° C. to 200° C., preferably 50° C. to 160° C., and more preferably 70° C. to 150° C. If Tg_al is within the above range, bending processability is good. The glass transition temperature of the alignment layer 5 is measured, for example, by TMA.
[0037] The liquid crystal layer 6 has a slow axis and a fast axis. The retardation Rd is the product of the difference Δn (Δn=ne-no) between the refractive index ne of the slow axis and the refractive index no of the fast axis and the dimension d of the liquid crystal layer 6 in the Z-axis direction. In other words, Rd can be calculated by the formula Rd=Δn×d.
[0038] 2(B), the liquid crystal layer 6 includes a plurality of liquid crystal molecules 61 aligned parallel to one another by the alignment layer 5. As viewed in the Z-axis direction, the long axis direction of the liquid crystal molecules 61 is the X-axis direction, and the short axis direction of the liquid crystal molecules 61 is the Y-axis direction. In this embodiment, the liquid crystal molecules 61 are rod-shaped liquid crystals, but may be discotic liquid crystals.
[0039] The liquid crystal layer 6 is formed by coating and drying a liquid crystal composition. The liquid crystal composition contains a photocurable liquid crystal containing an acrylic group or a methacrylic group. The liquid crystal composition may contain a component that does not show a liquid crystal phase by itself. It is sufficient that a liquid crystal phase is generated by polymerization. As the component that does not show a liquid crystal phase, for example, a monofunctional (meth)acrylate, a bifunctional (meth)acrylate, a trifunctional or higher (meth)acrylate, etc. are used. The liquid crystal composition may contain a photocurable monomer. The polymerizable liquid crystal composition may contain an additive. As the additive, a polymerization initiator, a surfactant, a chiral agent, a polymerization inhibitor, an ultraviolet absorber, an antioxidant, a light stabilizer, an antifoaming agent, or a dichroic dye is used. A plurality of types of additives may be used in combination.
[0040] The liquid crystal composition may be applied by a general method, such as spin coating, bar coating, extrusion coating, direct gravure coating, reverse gravure coating, or die coating. The solvent of the liquid crystal composition is removed by heating after application.
[0041] The solvent of the liquid crystal composition is, for example, an organic solvent. The organic solvent is an alcohol (for example, isopropyl alcohol), an amide (for example, N,N-dimethylformamide), a sulfoxide (for example, dimethyl sulfoxide), a hydrocarbon (for example, benzene or hexane), an ester (for example, methyl acetate, ethyl acetate, butyl acetate, or propylene glycol monoethyl ether acetate), a ketone (for example, acetone, cyclohexanone, or methyl ethyl ketone), or an ether (for example, tetrahydrofuran or 1,2-dimethoxyethane). Two or more kinds of organic solvents may be used in combination. The liquid crystal layer 6 may be formed by a vapor deposition method or a vacuum injection method that does not use a solvent.
[0042] The liquid crystal composition used may have a positive or negative wavelength dispersion of the Δn value after curing.
[0043] The liquid crystal composition contains, as a polymerizable compound, for example, compounds represented by the following formulas (a-1) to (a-13).
[0044] [ka]
[0045] [ka]
[0046] [ka] In the above formulae (a-5) and (a-8), n is an integer of 2 to 6. In the above formulae (a-6) and (a-7), R is an alkyl group having 3 to 6 carbon atoms. In the above formulae (a-11), (a-12), and (a-13), n means "normal" and indicates linearity.
[0047] The thickness T3 of the liquid crystal layer 6 (see FIG. 2) is determined based on the wavelength of light, the phase difference, and Δn (Δn=ne-no). For example, when the wavelength of light is 543 nm and the phase difference is 1 / 4 wavelength, Rd is 136 nm. When Rd is 136 nm and Δn is 0.1, the thickness T3 of the liquid crystal layer 6 is 1360 nm.
[0048] The thickness T3 of the liquid crystal layer 6 is determined based on the wavelength of light, the phase difference, and Δn as described above, and is not particularly limited, but is, for example, 0.3 μm to 30 μm, preferably 0.5 μm to 20 μm, and more preferably 0.8 μm to 10 μm. If T3 is 0.3 μm or more, the target phase difference is easily obtained. If T3 is 30 μm or less, the liquid crystal molecules 61 are easily aligned.
[0049] The liquid crystal layer 6 is not limited to a quarter-wave plate, but may be a half-wave plate or the like. The liquid crystal layer 6 is not limited to a retardation layer that shifts the phase between two orthogonal linearly polarized light components, but may be a compensation layer. The compensation layer corrects, for example, the phase difference that occurs at different viewing angles of the liquid crystal display, and improves the contrast of the screen within a specified viewing angle.
[0050] The thickness T3 of the liquid crystal layer 6 is measured in the normal direction at each point on the surface 41 of the transparent substrate 4. When the alignment layer 5 has grooves 52, in this specification, the thickness T3 of the liquid crystal layer 6 refers to the distance between the bottom of the grooves 52 and the surface of the liquid crystal layer 6 opposite the alignment layer 5.
[0051] The glass transition temperature Tg_a of the liquid crystal layer 6 is, for example, 50° C. to 200° C., and preferably 80° C. to 180° C. If Tg_a is within the above range, bending processability is good. The glass transition temperature Tg_a of the liquid crystal layer 6 is measured, for example, by TMA.
[0052] The thickness T4 of the retardation plate 3 is not particularly limited, but is, for example, 0.011 mm to 0.301 mm, preferably 0.021 mm to 0.101 mm, and more preferably 0.031 mm to 0.091 mm. The thickness T4 of the retardation plate 3 is measured in the normal direction at each point on the surface 41 of the transparent substrate 4.
[0053] The retarder 3 may be a broadband retarder further including a second liquid crystal layer laminated on the liquid crystal layer 6, although not shown. The number of liquid crystal layers included in the broadband retarder may be two or more, and may be three or more. When viewed in the Z-axis direction, the multiple liquid crystal layers have slow axes in different directions. When the retarder 3 includes multiple liquid crystal layers, it may include multiple alignment layers, or may have repeated pairs of liquid crystal layers and alignment layers. The multiple alignment layers may have the same material or different materials.
[0054] The retardation of the retarder 3 is not particularly limited, but if it is a quarter-wave plate, it is, for example, 100 nm to 180 nm, preferably 110 nm to 170 nm, and more preferably 120 nm to 160 nm. If the retarder 3 is a half-wave plate, it is, for example, 200 nm to 280 nm, preferably 210 nm to 270 nm, and more preferably 220 nm to 260 nm.
[0055] Second embodiment An optical element 1 according to the second embodiment will be described with reference to FIG. 3. Differences from the first embodiment will be mainly described below. Depending on the application, it is desirable for the optical element 1 to have a curved surface from the viewpoint of performance. For example, the optical element 1 includes a lens 2. The lens 2 may be a spherical lens or an aspheric lens. Furthermore, the lens 2 may be any of a biconcave lens, a plano-concave lens, a concave meniscus lens, a biconvex lens, a plano-convex lens, and a convex meniscus lens.
[0056] The lens 2 has a curved surface 21. The curved surface 21 has a radius of curvature of, for example, 10 mm to 100 mm on the entire surface or a part of the surface. The radius of curvature of the curved surface 21 is preferably 20 mm to 80 mm, and more preferably 50 mm to 70 mm. The curved surface 21 is a concave surface, for example, as shown in Fig. 3(A) and Fig. 3(B). The concave surface is a curved surface whose center of gravity P0 is recessed from the periphery. In both a cross section perpendicular to the X-axis direction and a cross section perpendicular to the Y-axis direction, the center of gravity P0 of the concave surface is recessed from the periphery of the concave surface. The X-axis direction, the Y-axis direction, and the Z-axis direction are mutually perpendicular. The Z-axis direction is the normal direction at the center of gravity P0 of the concave surface. The XY plane is parallel to the tangent plane at the center of gravity P0 of the concave surface.
[0057] In this embodiment, the curved surface 21 is a concave surface, but may be a convex surface as shown in Figures 4(B) and 4(C). A convex surface is a surface in which the center of gravity P0 is more convex (protrudes) than the periphery. In both a cross section perpendicular to the X-axis direction and a cross section perpendicular to the Y-axis direction, the center of gravity P0 of the convex surface is more convex than the periphery of the convex surface.
[0058] The outer shape of the lens 2 is not limited to the circular shape shown in FIG. 3C, but may be, for example, an ellipse or a polygon (including a rectangle).
[0059] The lens 2 may be made of resin or glass. The resin of the resin lens is, for example, polycarbonate, polyimide, polyacrylate, or cyclic olefin. The glass of the glass lens is, for example, BK7 or synthetic quartz.
[0060] The optical element 1 includes a retardation plate 3. The retardation plate 3 is curved along a curved surface 21 of the lens 2. The retardation plate 3 includes, for example, a transparent substrate 4, an alignment layer 5 formed on the transparent substrate 4, and a liquid crystal layer 6 formed on the alignment layer 5.
[0061] The retardation plate 3 is, for example, a quarter-wave plate. A quarter-wave plate may be used in combination with a linear polarizing plate (not shown). The linear polarizing plate may be disposed on the opposite side of the retardation plate 3 to the lens 2, between the retardation plate 3 and the lens 2, or on the opposite side of the retardation plate 3 to the lens 2.
[0062] The retardation plate 3 includes, for example, a transparent substrate 4, an alignment layer 5, and a liquid crystal layer 6 in this order from the lens 2 side as shown in Fig. 3(B). Note that, as shown in Figs. 4(A) and 4(C), the retardation plate 3 may include, in this order from the lens 2 side, a liquid crystal layer 6, an alignment layer 5, and a transparent substrate 4.
[0063] The thickness T1 (see FIG. 2) of the transparent substrate 4 is measured in the normal direction at each point on the curved surface 21 of the lens 2. The depth D (see FIG. 2) of the grooves 52 may be constant over the entire curved surface 21 of the lens 2, or may vary depending on the location, as described below. The pitch p of the grooves 52 may be constant over the entire curved surface 21 of the lens 2, or may vary depending on the location.
[0064] In this embodiment, the transparent substrate 4 is prepared separately from the lens 2 and provided on the curved surface 21 of the lens 2, but the transparent substrate 4 may be the lens 2. In the latter case, the alignment layer 5 is formed directly on the curved surface 21 of the lens 2.
[0065] Although not shown, the retarder 3 may be a broadband retarder further including a second liquid crystal layer laminated on the liquid crystal layer 6. The number of liquid crystal layers included in the broadband retarder may be two or more, and may be three or more. When viewed in the Z-axis direction, the multiple liquid crystal layers have slow axes in different directions from each other.
[0066] The broadband retardation plate is, for example, formed by alternately laminating alignment layers 5 and liquid crystal layers 6. The alignment layers 5 and the liquid crystal layers 6 are laminated in this order from the lens 2 side. Note that the broadband retardation plate may be formed by bonding a liquid crystal layer formed on a transparent substrate other than the lens 2 to a liquid crystal layer formed on the lens 2.
[0067] The retardation plate 3 is bent and bonded to the lens 2. The bonding layer 7 is, for example, a transparent optical adhesive (OCA), a liquid adhesive (OSA), polyvinyl butyral (PVB), ethylene vinyl acetate (EVA), cycloolefin polymer (COP), or thermoplastic polyurethane (TPU).
[0068] The phase difference (retardation) of the bonding layer 7 is, for example, 5 nm or less, and preferably 3 nm or less. From the viewpoint of reducing the variation in color tone, the phase difference of the bonding layer 7 is preferably as small as possible, and may be zero. The phase difference of the bonding layer 7 is measured, for example, by a parallel Nicol rotation method.
[0069] The glass transition point of the bonding layer 7 is, for example, −60° C. to 100° C., and preferably −40° C. to 50° C. If the glass transition point of the bonding layer 7 is within the above range, both bending workability and shape conformability can be achieved. The glass transition point of the bonding layer 7 is measured, for example, by TMA.
[0070] The thickness of the bonding layer 7 is, for example, 0.001 mm to 0.1 mm, and preferably 0.005 mm to 0.05 mm. If the thickness of the bonding layer 7 is within the above range, both bending workability and shape followability can be achieved. The thickness of the bonding layer 7 is measured in the normal direction at each point on the curved surface 21 of the lens 2.
[0071] The retardation plate 3 and the lens 2 are bonded together while being heated. The heating temperature is set based on the glass transition temperature Tgf of the transparent substrate 4, and is set within a range of, for example, (Tgf-10)°C or more and (Tgf+30)°C or less, and is preferably set within a range of (Tgf-10)°C or more and (Tgf+20)°C or less. Bonding of the retardation plate 3 and the lens 2 may be performed in a vacuum.
[0072] Alternatively, the retardation film 3 may be placed inside a metal mold for injection molding, and the lens 2 may be injection molded after bending the retardation film 3. When the lens 2 and the retardation film 3 are integrated by in-mold molding, the bonding layer 7 is not necessary.
[0073] Third embodiment Next, an optical element 1 according to a third embodiment etc. will be described. Below, differences from the second embodiment will be mainly described.
[0074] First, an optical element 1A according to a reference embodiment will be described with reference to Fig. 5 and Fig. 6. In Fig. 5C and Fig. 6C, the magnitude of Rd is expressed in gray scale. As the color approaches black from white, the magnitude of Rd of the optical element 1A increases.
[0075] The optical element 1A according to the reference embodiment includes a lens 2A and a retardation plate 3A. The retardation plate 3A includes a transparent substrate 4A, an alignment layer 5A, and a liquid crystal layer 6A. The lens 2A and the retardation plate 3A are bonded together via, for example, a bonding layer 7A.
[0076] When the retarder 3A is bent, the extension rate of the retarder 3A differs between the periphery and the center of the retarder 3A. As a result, the thickness of the retarder 3A and the thickness of the liquid crystal layer 6A change concentrically. Therefore, Rd shifts concentrically, and the color tone shifts concentrically. The extension rate (%) can be calculated from the formula "(A2-A1) / A1×100" where A1 is the dimension before bending and A2 is the dimension after bending.
[0077] For example, in the case where the curved surface 21A of the lens 2A is a concave surface as shown in Fig. 5(A), when the retarder 3A is bent as shown in Fig. 5(B), the thickness of the retarder 3A becomes continuously thinner from the periphery to the center of the retarder 3A. This is because the timing at which the periphery and the center of the retarder 3A come into contact with the curved surface 21A differs, and the center of the retarder 3A comes into contact with the curved surface 21A later than the periphery.
[0078] Therefore, as shown in Fig. 5(B), the thickness of the liquid crystal layer 6A becomes continuously thinner from the periphery to the center of the liquid crystal layer 6A. As a result, Rd becomes continuously smaller from the periphery to the center of the liquid crystal layer 6A as shown in Fig. 5(C). Therefore, the color tone shifts concentrically.
[0079] In addition, when the curved surface 21A of the lens 2A is a convex curved surface as shown in Fig. 6(A), when the retarder 3A is bent as shown in Fig. 6(B), the thickness of the retarder 3A becomes continuously thinner from the center to the periphery of the retarder 3A. This is because the timing at which the periphery and the center of the retarder 3A come into contact with the curved surface 21A differs, and the periphery of the retarder 3A comes into contact with the curved surface 21A later than the center.
[0080] Therefore, as shown in Fig. 6(B), the thickness of the liquid crystal layer 6A becomes continuously thinner from the center to the periphery of the liquid crystal layer 6A. As a result, Rd becomes continuously smaller from the center to the periphery of the liquid crystal layer 6A as shown in Fig. 6(C). Therefore, the color tone shifts concentrically.
[0081] 7 and 8, an optical element 1 according to this embodiment includes a lens 2 and a retardation plate 3. The retardation plate 3 includes a transparent substrate 4, an alignment layer 5, and a liquid crystal layer 6. The lens 2 and the retardation plate 3 are bonded together via, for example, an adhesive layer 7. The alignment layer 5 has a plurality of grooves 52 parallel to each other on a surface in contact with the liquid crystal layer 6.
[0082] When bending the retarder 3, the extension rate of the retarder 3 differs between the periphery and the center of the retarder 3. As a result, similar to the above-mentioned reference embodiment, after bending the retarder 3, the thickness T4 of the retarder 3 and the thickness T3 of the liquid crystal layer 6 differ between the periphery and the center of the retarder 3.
[0083] For example, in the case where the curved surface 21 of the lens 2 is a concave curved surface as shown in FIG. 7(A), when the retardation film 3 is bent, as described in the above reference embodiment, the thickness T4 of the retardation film 3 and the thickness T3 of the liquid crystal layer 6 become continuously thinner from the periphery to the center of the retardation film 3.
[0084] When the curved surface 21 of the lens 2 is a concave curved surface, the elongation of the retardation film 3 is as follows. The elongation of the retardation film 3 at the periphery of the retardation film 3 is, for example, 0.1% to 20%, and preferably 1% to 15%. The elongation of the retardation film 3 at the center of the retardation film 3 is, for example, 0.5% to 40%, and preferably 1% to 20%.
[0085] Furthermore, in the case where the curved surface 21 of the lens 2 is a convex curved surface as shown in FIG. 8(A), when the retardation film 3 is bent, as described in the above reference embodiment, the thickness T4 of the retardation film 3 and the thickness T3 of the liquid crystal layer 6 become continuously thinner from the center to the periphery of the retardation film 3.
[0086] When the curved surface 21 of the lens 2 is a convex curved surface, the elongation of the retardation film 3 is as follows: The elongation of the retardation film 3 at the center of the retardation film 3 is, for example, 0.1% to 20%, and preferably 1% to 15%. The elongation of the retardation film 3 at the periphery of the retardation film 3 is, for example, 0.5% to 40%, and preferably 1% to 20%.
[0087] Therefore, in the optical element 1 of this embodiment and the like, the depth D of the groove 52 at the portion where the thickness T4 of the retardation plate 3 is the thinnest is deeper than the depth D of the groove 52 at the portion where the thickness T4 of the retardation plate 3 is the thickest. The depth D of the groove 52 is adjusted by, for example, the concave-convex pattern of a mold used in the imprinting method. The depth D of the groove 52 can also be adjusted by partially ashing the surface 51 of the alignment layer 5.
[0088] The deeper the depth D of the groove 52, the stronger the alignment control force and the larger Δn. The increase in Rd due to the increase in Δn can offset the decrease in Rd due to the decrease in d, and the variation in Rd can be suppressed.
[0089] For example, when the curved surface 21 of the lens 2 is a concave curved surface as shown in Fig. 7(A), as is clear from a comparison of Fig. 7(B) and Fig. 7(C), the depth D of the grooves 52 at the center of the retardation film 3 is deeper than the depth D of the grooves 52 at the periphery of the retardation film 3. The depth D of the grooves 52 becomes deeper continuously or stepwise from the periphery to the center of the retardation film 3. Therefore, it is possible to suppress a concentric shift of Rd and a concentric shift of color tone.
[0090] Furthermore, when the curved surface 21 of the lens 2 is a convex curved surface as shown in Fig. 8(A), as is clear from a comparison of Fig. 8(B) and Fig. 8(C), the depth D of the grooves 52 at the periphery of the retardation film 3 is deeper than the depth D of the grooves 52 at the center of the retardation film 3. The depth D of the grooves 52 becomes deeper continuously or stepwise from the center to the periphery of the retardation film 3. Therefore, it is possible to suppress a concentric shift of Rd and a concentric shift of color tone. EXAMPLES
[0091] The experimental data will be explained below.
[0092] <Material> The materials were as follows: Monomer B1: AGC product name "C6FMA" perfluorohexylethyl methacrylate Monomer B2: Shin-Nakamura Chemical Co., Ltd. product name "NK Ester A-DCP", dimethylol-tricyclodecane diacrylate Monomer B3: Shin-Nakamura Chemical Co., Ltd. product name "NK Ester A-HD-N", 1,6-hexanediol diacrylate Monomer B4: Shin-Nakamura Chemical Co., Ltd. product name "DPHA" Surfactant C1: AGC Seimi Chemical Co., Ltd. product name "Surflon S-651" Surfactant C2: Neos product name "Futergent 710FL" Surfactant C3: BYK product name "BYK327" Liquid crystal D1: BASF product name "LC242" Photopolymerization initiator E1: Ciba Specialty Chemicals product name "IRGACURE907" Solvent F1: Methyl ethyl ketone Transparent substrate G1: TAC film (Fujifilm ZRD40SL, thickness 40 μm).
[0093] <Photocurable composition A1~A13> Photocurable compositions A1 to A13 were prepared in the amounts shown in Table 1.
[0094] [Table 1] Photocurable compositions A1 to A13 were all solvent-free compositions that did not contain a solvent. Photocurable compositions A12 and A13 were cloudy and did not transmit light well, and therefore were unsuitable for use as an alignment layer.
[0095] <Liquid crystal composition L1> 100 g of liquid crystal D1 and 3.0 g of photopolymerization initiator E1 were mixed, and the resulting mixture was diluted with solvent F1 so that the solid content concentration was 25% by mass, to obtain liquid crystal composition L1.
[0096] <Liquid crystal composition L2> 100 g of liquid crystal D1, 0.4 g of surfactant C1, and 3.0 g of photopolymerization initiator E1 were mixed, and the resulting mixture was diluted with solvent F1 to a solids concentration of 25% by mass, to obtain liquid crystal composition L2.
[0097] <Molds M1 to M7> The molds M1 to M7 were as follows. Mold M1: A pattern of protrusions and recesses with a groove pitch of 90 nm and a groove depth of 130 nm is created on a silicon wafer by photolithography. Mold M2: A pattern of protrusions and recesses with a groove pitch of 140 nm and a groove depth of 130 nm was created on a silicon wafer using photolithography. Mold M3: Edmund Holographic Diffraction Grating 3600GPM VIS 50mm Mold M4: Edmund Holographic Diffraction Grating 2400GPM VIS 50mm Mold M5: Edmund Holographic Diffraction Grating 1800GPM VIS 50mm Mold M6: Edmund Holographic Diffraction Grating 1200GPM VIS 50mm Mold M7: Edmund blazed diffraction grating 900GPM 500nm 25mm.
[0098] <Mold M8> The mold M8 was prepared by the following procedure: First, the photocurable composition A1 was sandwiched between the mold M1 and a PET film (Cosmoshine A4300, manufactured by Toyobo Co., Ltd., thickness 250 μm), and 1000 mJ / cm 2 was applied to the photocurable composition A1 through the PET film while maintaining the gap at 5 μm. 2 The photocurable composition A1 was cured by irradiating it with ultraviolet light. Thereafter, the mold M1 was peeled off to prepare a mold M1-2. The concave-convex pattern of the mold M1-2 was an inverse of the concave-convex pattern of the mold M1.
[0099] The mold M1-2 was ashed for 5 minutes in a vacuum at 200 ml / min oxygen and 400 W power. Thereafter, the photocurable composition A1 was sandwiched between the mold M1-2 and a PET film (Cosmoshine A4300, manufactured by Toyobo Co., Ltd., thickness 250 μm), and 1000 mJ / cm was applied to the photocurable composition A1 through the PET film while maintaining the gap at 5 μm. 2 The photocurable composition A1 was cured by irradiating it with ultraviolet light. After that, the mold M1-2 was peeled off to prepare the mold M8. The concave-convex pattern of the mold M8 was the inverse of the concave-convex pattern of the mold M1-2. The depth of the grooves of the mold M8 was 25 nm.
[0100] <Mold M9> Mold M9 was prepared in the same manner as mold M8, except that mold M2 was used instead of mold M1 and the ashing time was 8 minutes. The groove depth of mold M9 was 40 nm.
[0101] <Mold M10> Mold M10 was prepared in the same manner as mold M8, except that mold M2 was used instead of mold M1 and the ashing time was 12 minutes. The groove depth of mold M10 was 15 nm.
[0102] <Optical elements> In the following Examples 1 to 49, optical elements were produced using the above-mentioned photocurable compositions A1 to A11, the above-mentioned molds M1 to M10, and the above-mentioned liquid crystal compositions L1 to L2. The following Examples 2 to 12, 14, 16, 18, 24, 26, 28, 30, 32, 34, 36, 38 to 39, 41, 43, 45 to 46, and 48 are working examples, and the following Examples 1, 13, 15, 17, 19 to 23, 25, 27, 29, 31, 33, 35, 37, 40, 42, 44, 47, and 49 are comparative examples.
[0103] (Example 1) The alignment layer was prepared by the following procedure: First, the photocurable composition A1 was sandwiched between the mold M2 and the transparent substrate G1, and while maintaining the gap between them at 5 μm, 1000 mJ / cm 2 was applied to the photocurable composition A1 through the transparent substrate G1. 2 The photocurable composition A1 was cured by irradiating it with ultraviolet light of 1000 nm, and then the mold M2 was peeled off to produce a laminate consisting of the alignment layer having the unevenness formed thereon and the transparent substrate G1.
[0104] The liquid crystal layer was prepared by the following procedure. First, the liquid crystal composition L1 was applied by spin coating to the uneven surface of the alignment layer, and dried at 90° C. for 5 minutes to form a liquid film with a thickness of 1 μm. 2 The liquid film was irradiated with ultraviolet light to cure the liquid crystal composition L1, thereby obtaining an optical element including a liquid crystal layer, an alignment layer, and a transparent substrate.
[0105] (Example 2) An optical element was produced in the same manner as in Example 1, except that the photocurable composition A2 was used instead of the photocurable composition A1.
[0106] (Example 3) An optical element was produced in the same manner as in Example 1, except that the photocurable composition A3 was used instead of the photocurable composition A1.
[0107] (Example 4) An optical element was produced in the same manner as in Example 1, except that the photocurable composition A4 was used instead of the photocurable composition A1.
[0108] (Example 5) An optical element was produced in the same manner as in Example 1, except that the photocurable composition A5 was used instead of the photocurable composition A1.
[0109] (Example 6) An optical element was produced in the same manner as in Example 1, except that the photocurable composition A6 was used instead of the photocurable composition A1.
[0110] (Example 7) An optical element was produced in the same manner as in Example 1, except that the photocurable composition A7 was used instead of the photocurable composition A1.
[0111] (Example 8) An optical element was produced in the same manner as in Example 1, except that the photocurable composition A8 was used instead of the photocurable composition A1.
[0112] (Example 9) An optical element was produced in the same manner as in Example 1, except that Photocurable Composition A9 was used instead of Photocurable Composition A1.
[0113] (Example 10) An optical element was produced in the same manner as in Example 1, except that the photocurable composition A10 was used instead of the photocurable composition A1.
[0114] (Example 11) An optical element was produced in the same manner as in Example 1, except that the photocurable composition A11 was used instead of the photocurable composition A1.
[0115] (Example 12) An optical element was produced in the same manner as in Example 1, except that the photocurable composition A9 was used instead of the photocurable composition A1, and the mold M1 was used instead of the mold M2.
[0116] (Example 13) An optical element was produced in the same manner as in Example 1, except that the mold M1 was used instead of the mold M2.
[0117] (Example 14) An optical element was produced in the same manner as in Example 1, except that the photocurable composition A9 was used instead of the photocurable composition A1, and the mold M3 was used instead of the mold M2.
[0118] (Example 15) An optical element was produced in the same manner as in Example 1, except that the mold M3 was used instead of the mold M2.
[0119] (Example 16) An optical element was produced in the same manner as in Example 1, except that Photocurable Composition A9 was used instead of Photocurable Composition A1, and Mold M4 was used instead of Mold M2.
[0120] (Example 17) An optical element was produced in the same manner as in Example 1, except that mold M4 was used instead of mold M2.
[0121] (Example 18) An optical element was produced in the same manner as in Example 1, except that Photocurable Composition A9 was used instead of Photocurable Composition A1, and Mold M5 was used instead of Mold M2.
[0122] (Example 19) An optical element was produced in the same manner as in Example 1, except that mold M5 was used instead of mold M2.
[0123] (Example 20) An optical element was produced in the same manner as in Example 1, except that the photocurable composition A9 was used instead of the photocurable composition A1, and the mold M6 was used instead of the mold M2.
[0124] (Example 21) An optical element was produced in the same manner as in Example 1, except that the mold M6 was used instead of the mold M2.
[0125] (Example 22) An optical element was produced in the same manner as in Example 1, except that Photocurable composition A9 was used instead of Photocurable composition A1, and mold M7 was used instead of mold M2.
[0126] (Example 23) An optical element was produced in the same manner as in Example 1, except that mold M7 was used instead of mold M2.
[0127] (Example 24) An optical element was produced in the same manner as in Example 1, except that Photocurable Composition A9 was used instead of Photocurable Composition A1, and Mold M8 was used instead of Mold M2.
[0128] (Example 25) An optical element was produced in the same manner as in Example 1, except that mold M8 was used instead of mold M2.
[0129] (Example 26) An optical element was produced in the same manner as in Example 1, except that the photocurable composition A9 was used instead of the photocurable composition A1, and the mold M9 was used instead of the mold M2.
[0130] (Example 27) An optical element was produced in the same manner as in Example 1, except that mold M9 was used instead of mold M2.
[0131] (Example 28) An optical element was produced in the same manner as in Example 1, except that the photocurable composition A9 was used instead of the photocurable composition A1, and the mold M10 was used instead of the mold M2.
[0132] (Example 29) An optical element was produced in the same manner as in Example 1, except that the mold M10 was used instead of the mold M2.
[0133] (Example 30) An optical element was prepared in the same manner as in Example 1, except that photocurable composition A10 was used instead of photocurable composition A1, liquid crystal composition L2 was used instead of liquid crystal composition L1, and mold M1 was used instead of mold M2.
[0134] (Example 31) An optical element was produced in the same manner as in Example 1, except that the liquid crystal composition L2 was used instead of the liquid crystal composition L1, and the mold M1 was used instead of the mold M2.
[0135] (Example 32) An optical element was produced in the same manner as in Example 1, except that the photocurable composition A10 was used instead of the photocurable composition A1, and the liquid crystal composition L2 was used instead of the liquid crystal composition L1.
[0136] (Example 33) An optical element was prepared in the same manner as in Example 1, except that the liquid crystal composition L2 was used instead of the liquid crystal composition L1.
[0137] (Example 34) An optical element was prepared in the same manner as in Example 1, except that photocurable composition A10 was used instead of photocurable composition A1, liquid crystal composition L2 was used instead of liquid crystal composition L1, and mold M5 was used instead of mold M2.
[0138] (Example 35) An optical element was produced in the same manner as in Example 1, except that the liquid crystal composition L2 was used instead of the liquid crystal composition L1, and the mold M5 was used instead of the mold M2.
[0139] (Example 36) An optical element was produced in the same manner as in Example 1, except that photocurable composition A9 was used instead of photocurable composition A1, the thickness T3 of the liquid crystal layer was set to 2 μm, and mold M1 was used instead of mold M2.
[0140] (Example 37) An optical element was produced in the same manner as in Example 1, except that the thickness T3 of the liquid crystal layer was set to 2 μm and the mold M1 was used instead of the mold M2.
[0141] (Example 38) An optical element was produced in the same manner as in Example 1, except that the photocurable composition A10 was used instead of the photocurable composition A1 and the thickness T3 of the liquid crystal layer was set to 2 μm.
[0142] (Example 39) An optical element was produced in the same manner as in Example 1, except that the photocurable composition A9 was used instead of the photocurable composition A1, and the thickness T3 of the liquid crystal layer was set to 2 μm.
[0143] (Example 40) An optical element was prepared in the same manner as in Example 1, except that the thickness T3 of the liquid crystal layer was set to 2 μm.
[0144] (Example 41) An optical element was produced in the same manner as in Example 1, except that photocurable composition A9 was used instead of photocurable composition A1, the thickness T3 of the liquid crystal layer was set to 2 μm, and mold M5 was used instead of mold M2.
[0145] (Example 42) An optical element was produced in the same manner as in Example 1, except that the thickness T3 of the liquid crystal layer was set to 2 μm and the mold M5 was used instead of the mold M2.
[0146] (Example 43) An optical element was prepared in the same manner as in Example 1, except that photocurable composition A9 was used instead of photocurable composition A1, liquid crystal composition L2 was used instead of liquid crystal composition L1, the thickness T3 of the liquid crystal layer was set to 2 μm, and mold M1 was used instead of mold M2.
[0147] (Example 44) An optical element was produced in the same manner as in Example 1, except that liquid crystal composition L2 was used instead of liquid crystal composition L1, the thickness T3 of the liquid crystal layer was set to 2 μm, and mold M1 was used instead of mold M2.
[0148] (Example 45) An optical element was prepared in the same manner as in Example 1, except that photocurable composition A10 was used instead of photocurable composition A1, liquid crystal composition L2 was used instead of liquid crystal composition L1, and the thickness T3 of the liquid crystal layer was 2 μm.
[0149] (Example 46) An optical element was prepared in the same manner as in Example 1, except that photocurable composition A9 was used instead of photocurable composition A1, liquid crystal composition L2 was used instead of liquid crystal composition L1, and the thickness T3 of the liquid crystal layer was 2 μm.
[0150] (Example 47) An optical element was prepared in the same manner as in Example 1, except that liquid crystal composition L2 was used instead of liquid crystal composition L1 and the thickness T3 of the liquid crystal layer was set to 2 μm.
[0151] (Example 48) An optical element was prepared in the same manner as in Example 1, except that photocurable composition A9 was used instead of photocurable composition A1, liquid crystal composition L2 was used instead of liquid crystal composition L1, the thickness T3 of the liquid crystal layer was set to 2 μm, and mold M5 was used instead of mold M2.
[0152] (Example 49) An optical element was produced in the same manner as in Example 1, except that liquid crystal composition L2 was used instead of liquid crystal composition L1, the thickness T3 of the liquid crystal layer was set to 2 μm, and mold M5 was used instead of mold M2.
[0153] <Depth D and pitch p of grooves in alignment layer> The depth D and pitch p of the grooves of the alignment layers produced in Examples 1 to 49 were measured by cross-sectional SEM observation. More specifically, D and p were each measured at five points and the average value was calculated.
[0154] <Fluorine element concentration FC on the surface of the alignment layer> The fluorine element concentration FC on the surface of the alignment layer was measured by X-ray photoelectron spectroscopy (XPS). Since the detection depth in XPS is very shallow at about 5 nm, the measured value of XPS was adopted as FC. The measurement conditions for XPS were as follows: Equipment used: Thermo Fisher K-Alpha Analysis size: Φ0.4mm Capture Area Survey scan; 0eV~1350eV Narrow scan; F1s, C1s, O1s, N1s Pass energy Survey scan; 1eV Narrow scan; 0.1 eV.
[0155] <Retardation of optical elements> The retardation Rd of the optical elements produced in Examples 1 to 49 was measured using Photal manufactured by Otsuka Electronics Co., Ltd. Here, Rd is the retardation of light with a wavelength of 589 nm. The average value of measurements taken at five random points within the plane was taken as the measured value.
[0156] <Presence or absence of diffracted light> The presence or absence of diffracted light in the optical elements prepared in Examples 1 to 49 was confirmed by irradiating the transparent substrate side of the optical element with white LED light and observing it from the liquid crystal layer side.
[0157] <Summary> Table 2 shows the evaluation results of Examples 1 to 11. In Table 2, "◯" means that an improvement effect on retardation Rd was observed, and "×" means that an improvement effect on retardation Rd was not observed. In Tables 3 to 7, "◯" and "×" have the same meaning.
[0158] [Table 2] As is clear from Table 2, in Examples 2 to 12, unlike Example 1, the alignment layer contained at least one of a fluorine element and a surfactant, and therefore Rd was larger than that of Example 1. In addition, in Examples 1 to 12, the groove pitch p was 300 nm or less, so no diffracted light was generated.
[0159] Table 3 shows the evaluation results of Examples 1, 9 and 12 to 23.
[0160] [Table 3] As is clear from Table 3, in Examples 12, 9, 14, 16 and 18, unlike Examples 13, 1, 15, 17 and 19, the alignment layer contained fluorine element and surfactant, so Rd could be increased compared to Examples 13, 1, 15, 17 and 19. However, in Examples 20 and 22, unlike Examples 21 and 23, the alignment layer contained fluorine element and surfactant, but Rd could not be increased compared to Examples 21 and 23. From Table 3, it can be seen that if the groove pitch p is greater than 600 nm, the improvement effect of Rd cannot be obtained even if the alignment layer contains fluorine element and surfactant. Also, in Examples 1, 9 and 12 to 15, unlike Examples 16 to 23, the groove pitch p was 300 nm or less, so no diffracted light was generated.
[0161] Table 4 shows the evaluation results of Examples 24 to 29.
[0162] [Table 4] As is clear from Table 4, in Examples 24, 26 and 28, unlike Examples 25, 27 and 29, the alignment layer contained elemental fluorine and a surfactant, and therefore Rd was larger than in Examples 25, 27 and 29. From Table 4, it can be seen that if the groove depth D is 3 nm or more, the effect of the alignment layer containing at least one of elemental fluorine and a surfactant can be obtained.
[0163] Table 5 shows the evaluation results of Examples 30 to 35.
[0164] [Table 5] As is clear from Table 5, in Examples 30, 32 and 34, unlike Examples 31, 33 and 35, the alignment layer contained elemental fluorine and a surfactant, and therefore Rd was larger than in Examples 31, 33 and 35. Also, in Example 32, unlike Example 10, a liquid crystal composition containing a surfactant (liquid crystal composition L2) was used, and therefore Rd was larger than in Example 10, which used liquid crystal composition L1. It can be seen that when the liquid crystal composition contains a surfactant, the difference in Rd caused by whether or not the alignment layer contains elemental fluorine and a surfactant becomes smaller (see Examples 1, 10, 32 and 33).
[0165] Table 6 shows the evaluation results of Examples 36 to 42.
[0166] [Table 6] As is clear from Table 6, in Examples 36, 38 to 39 and 41, unlike Examples 37, 40 and 42, the alignment layer contained elemental fluorine and a surfactant, and therefore Rd was larger than in Examples 37, 40 and 42. Furthermore, in Examples 36, 39 and 41, the thickness T3 of the liquid crystal layer was twice that of Examples 12, 9 and 19, but the effect of the alignment layer containing elemental fluorine and a surfactant was obtained.
[0167] Table 7 shows the evaluation results of Examples 43 to 49.
[0168] [Table 7] As is clear from Table 7, in Examples 43, 45 to 46, and 48, unlike Examples 44, 47, and 49, the alignment layer contained fluorine element and a surfactant, and therefore Rd was larger than that of Examples 44, 47, and 49. In Example 45, the thickness T3 of the liquid crystal layer was twice that of Example 32, but the effect of the alignment layer containing fluorine element and a surfactant was obtained. In Examples 43, 45 to 46, and 48, unlike Examples 36, 38 to 39, and 41, a liquid crystal composition containing a surfactant (liquid crystal composition L2) was used, and therefore Rd was larger than that of Examples 36, 38 to 39, and 41, which used liquid crystal composition L1.
[0169] Although the optical element according to the present disclosure has been described above, the present disclosure is not limited to the above-mentioned embodiments. Various changes, modifications, substitutions, additions, deletions, and combinations are possible within the scope of the claims. These naturally fall within the technical scope of the present disclosure.
[0170] This application claims priority based on Japanese Patent Application No. 2020-135092 filed with the Japan Patent Office on August 7, 2020, and Japanese Patent Application No. 2020-180362 filed with the Japan Patent Office on October 28, 2020, and the entire contents of Japanese Patent Application No. 2020-135092 and Japanese Patent Application No. 2020-180362 are incorporated by reference into this application. [Explanation of symbols]
[0171] 1 Optical elements 2 Lenses 3 Retardation plate 4 Transparent base material 5. Alignment layer 6 Liquid crystal layer
Claims
1. An optical element including a retardation plate that is curved along a curved surface, the retardation plate includes a transparent substrate, an alignment layer formed on the transparent substrate, and a liquid crystal layer formed on the alignment layer; a surface of the alignment layer in contact with the liquid crystal layer is formed with a plurality of parallel grooves for aligning liquid crystal molecules of the liquid crystal layer; the pitch of the grooves is 10 nm to 600 nm; The alignment layer is a copolymer of an energy curable composition and contains a fluorine element on the surface thereof. an optical element, wherein a depth of the groove at a portion where the retardation plate is thinnest is greater than a depth of the groove at a portion where the retardation plate is thickest.
2. 2. The optical element according to claim 1, wherein the surface of the alignment layer has a fluorine element concentration of 0.1 atomic % to 50 atomic %.
3. The optical element according to claim 1 , wherein the alignment layer comprises a surfactant.
4. An optical element including a retardation plate curved along a curved surface, the retardation plate includes a transparent substrate, an alignment layer formed on the transparent substrate, and a liquid crystal layer formed on the alignment layer; a surface of the alignment layer in contact with the liquid crystal layer is formed with a plurality of parallel grooves for aligning liquid crystal molecules of the liquid crystal layer; the pitch of the grooves is 10 nm to 600 nm; The alignment layer is a copolymer of an energy curable composition and contains a surfactant, an optical element, wherein a depth of the groove at a portion where the retardation plate is thinnest is greater than a depth of the groove at a portion where the retardation plate is thickest.
5. 5. The optical element according to claim 3, wherein the content of the surfactant in the alignment layer is 0.05% by mass to 4% by mass.
6. 6. The optical element according to claim 1, wherein the liquid crystal layer has a thickness of 0.3 μm to 30 μm.
7. 7. The optical element according to claim 1, wherein the liquid crystal layer is a retardation layer or a compensation layer.
8. 8. The optical element according to claim 1, wherein the groove has a depth of 3 nm to 500 nm.
Citation Information
Patent Citations
Manufacturing method for patterned optical elements
JP2005516236A
Liquid crystal device
JP2013007781A
Phase difference film and liquid crystal display device
JP2014006356A
Retardation film, and manufacturing method of retardation film
JP2014089346A
Alignment film for liquid crystal lens and mold for forming same
JP2016509966A